THE DEVELOPMENT OF MANAGEMENT MODEL ON COLLABORATIVE-BASED STUDENTS' SCIENTIFIC WRITING MENTORING THROUGH AN ONLINE RESEARCH CLINIC APPROACH AT UPBJJ-UT SEMARANG - Binti Muflikah; Swidarto Swidarto; Vica Ananta Kusuma (ETERNAL (English Teaching Journal), 2021)
Scientific writing plays a crucial role in determining the quality of students and universities. So far, the ability of students to establish scientific works is varied. Some students can produce scientific work in an APIK (Asli, Penting, Ilmiah, Konsisten) way which means Original, Important, Scientific, and Consistent), as well as in a "SMART" (Specific, Manageable, Acceptable, Realistic and Time-bound) way. However, some of them also encounter difficulties so they need assistance on a collaborative based scientific writing through Online Research Clinic (ORC) approach. Collaborative-based mentoring can build collegiality and collaboration among tutors, students, and UPBJJ-UT managers. Effective mentoring requires an ORC approach. An online research clinic is a place designed to help students who have difficulty writing scientific papers through clinical methods, starting from problem identification, diagnosis, prognosis, synthesis, treatment, reflection using internet / online network media such as website, email, WhatsApp, telegram, Google classroom, webinars, zoom and so on. Online Research Clinic is a solution to solve students' difficulties in writing scientific papers. The existence of ORC is an innovation to create independent learning in the digital era due to its flexibility and easy accessibility at all times both face-to-face and online. Besides, it is also used by tutors and managers to collaborate in providing consultation services to students. This study aims to analyze and synthesize the management model of scientific work mentoring with a proper online clinical research approach for UPJJB-UT Semarang students. The research method uses Research and Development. Data obtained from the results of scientific work mentoring, needs analysis, testing, and model validation. Data collection techniques use questionnaires, interviews, documentation studies, observation, and FGD. The validity test uses model validation from experts and practitioners. The qualitative descriptive analysis uses data displays, data reduction, data verification, and conclusion. The results of the study conclude that the mentoring management model implemented so far was categorized as sufficient, still theoretical, and not practical yet. ORC assistance model is very important and needed because it is practical, effective, and efficient. The ORC mentoring model is very feasible so that it can be implemented to improve the quality of students in producing scientific papers for fulfilling assignments, requirements for completing study program, and scientific publications.